Digenic inheritance of human primary microcephaly delineates centrosomal and non‐centrosomal pathways. Issue 2 (27th November 2019) - Duerinckx, Sarah; Jacquemin, Valérie; Drunat, Séverine; Vial, Yoann; Passemard, Sandrine; Perazzolo, Camille; Massart, Annick; Soblet, Julie; Racapé, Judith; Desmyter, Laurence; Badoer, Cindy; Papadimitriou, Sofia; et al.
Abstract: Primary microcephaly (PM) is characterized by a small head since birth and is vastly heterogeneous both genetically and phenotypically. While most cases are monogenic, genetic interactions between Aspm and Wdr62 have recently been described in a mouse model of PM. Here, we used two complementary, holistic in vivo approaches: high throughput DNA sequencing of multiple PM genes in human patients with PM, and genome‐edited zebrafish modeling for the digenic inheritance of PM. Exomes of patients with PM showed a significant burden of variants in 75 PM genes, that persisted after removing monogenic causes of PM (e.g., biallelic pathogenic variants in CEP152 ). This observation was replicated in an independent cohort of patients with PM, where a PM gene panel showed in addition that the burden was carried by six centrosomal genes. Allelic frequencies were consistent with digenic inheritance. In zebrafish, non‐centrosomal gene casc5 −/− produced a severe PM phenotype, that was not modified by centrosomal genes aspm or wdr62 invalidation. A digenic, quadriallelic PM phenotype was produced by aspm and wdr62 . Our observations provide strong evidence for digenic inheritance of human PM, involving centrosomal genes. Absence of genetic interaction between casc5 and aspm or wdr62 further delineates centrosomal and non‐centrosomal pathways in PM. Abstract : In a cohort of patients with primary microcephaly (PM), exome sequencing showed a significant burden of variants in PM genes, that persisted after removing monogenic causes of PM. The finding was confirmed in a replication cohort (not shown), and candidate centrosomal gene pairs were identified. Zebrafish genome editing produced a severe PM phenotype in casc5 −/− and no phenotype in aspm −/− or wdr62 −/− fishes. Zebrafish crosses displayed digenic interactions between centrosomal genes aspm and wdr62, and no interactions between non‐centrosomal gene casc5 and either aspm or wdr62, delineating centrosomal and non‐centrosomal pathways in PM. * p  = .028.